ABCB4 disease mimicking morbus Wilson: A potential diagnostic pitfall - Sticova, Eva; Neroldova, Magdalena; Kotalova, Radana; Subhanova, Iva; Jirsa, Milan (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2020)
INTRODUCTION: Progressive familial intrahepatic cholestasis type 3 (PFIC3) is a rare autosomal recessive cholestatic liver disorder caused by genetic deficiency of ATP-binding cassette subfamily B member 4 (ABCB4), a hepatocanalicular floppase translocating phospholipids from the inner to the outer leaflet of the canalicular membrane lipid bilayer. PFIC3 is characterised by production of hydrophilic bile with lithogenic properties which is harmful to the hepatobiliary epithelia. Chronic cholestasis in some patients may be accompanied by excessive accumulation of copper in the liver and by increased urinary copper excretion, the findings mimicking Wilson disease (WD). METHODS AND RESULTS: We report an 11 y/o male patient with growth retardation, mild craniofacial dysmorphic features and chronic liver disease, initially diagnosed and treated as WD. Whereas genetic testing for WD was negative, further molecular and histopathological analysis revealed two novel mutations (c.833+1G>T and c.1798T>A) in ABCB4 and complete absence of the ABCB4/MDR3 protein in the liver, determining PFIC3 as the correct diagnosis. CONCLUSION: PFIC3 and WD display pleomorphic and sometimes overlapping clinical and laboratory features, which may pose a differential diagnostic problem. Since the patient management in WD and PFIC3 differs significantly, an early and accurate diagnosis is crucial for optimising of therapeutic approach and prevention of possible complications.
Keywords: diferenciální diagnóza; hepatolentikulární degenerace; Wilson disease; ATP7B; ABCB4; mužské pohlaví; ATP Binding Cassette Transporter, Subfamily B; dítě; Child; intrahepatální cholestáza; Humans; copper metabolism; Hepatolenticular Degeneration; Diagnosis, Differential; P-glykoproteiny; progressive familial intrahepatic cholestasis type 3; lidé; Male; Cholestasis, Intrahepatic